Exploring the challenges and strategies in learning to speak English: The lived experiences of EFL students - Sawitry, Maryanti; Harlina Harja; Hidayati, Sri; Turiyati, Turiyati; Indrayanti, Iin (Indonesian Research Journal in Education |IRJE|, 2026)
This study examines the challenges and strategies that EFL students face in learning to speak English in Batang Hari, Indonesia. Employing a phenomenological approach, the study investigates the lived experiences of six students from the English Tadris Department at a private university. Data were collected through in-depth, semi-structured interviews. The findings reveal that students face significant difficulties, including limited vocabulary, low confidence, and pronunciation issues, which hinder their speaking proficiency. To overcome these challenges, students utilized strategies such as peer support, self-recording, and the use of multimedia tools. These strategies helped improve their speaking abilities and build greater confidence. This study highlights the importance of incorporating supportive learning strategies and a positive environment to enhance English speaking skills. The findings provide valuable insights for educators seeking to address speaking challenges in rural EFL contexts and inform future teaching practices.